A case report of black swan (Cygnus atratus) died from gastric perforation and secondary infection resulting from ingestion of cloth—like foreign material - Jiao, Xianqin; Wang, Haoqian; Yan, Yongchao; Codjia, Cossi Remi; Wang, Xinwei (Frontiers in Veterinary Science, 2025)
In this case, the cause of death of black swan was determined by investigating the daily feeding situation of black swan and combining clinical diagnosis, pathological anatomy, PCR detection and other methods. Clinical autopsy results showed that the dead black swan was dehydrated and emaciated with its stomach filled with large amounts of fine sand and black cloth. The main pathological manifestations were peritonitis, air sac inflammation, perihepatic inflammation and necrosis, pericarditis, and dendritic pancreatic hemorrhage. Simultaneously Shigella boydii, Escherichia coli and Enterococcus faecalis were isolated from black swan bodies. The clinical evidence above showed that the swan died of ingesting human fabric, which blocked its stomach and caused a perforation, followed by a secondary bacterial infection. It is the first reported swan death caused because of eating human-cloth waste, suggesting that humans still need to work hard to protect the environment and care for animals.